Ecology of the forest microbiome: Highlights of temperate and boreal ecosystems. (December 2016) - Uroz, S.; Buée, M.; Deveau, A.; Mieszkin, S.; Martin, F.
Abstract: Due to land use history, most of the current temperate and boreal forests are developed on nutrient-poor and rocky soils, keeping fertile soils for agriculture. Consequently, the conditions occurring in forest ecosystems strongly differ from those of other terrestrial environments, giving importance to the access of nutritive elements and their recycling for the long-lasting development of forest ecosystems. In this review, we present an overview of the recent findings on the relationships between bacterial and fungal communities and their tree hosts at both the taxonomic and functional levels. We highlighted the common and different deterministic drivers of these microbial communities, focusing on the tree species effect, the different interfaces existing between the trees and their environment, the impact of tree by-products (decaying wood and litter), the impact of soil and seasonal changes, and lastly, the consequences of forestry practices. Depicting both taxonomic and functional diversity based on cultivation-dependent and -independent analyses, we highlight the distribution patterns and the functional traits characterizing bacterial and fungal communities. We also discuss the importance of bridging environmental microbiology to genomics and how to integrate the interactions between microorganisms for a better understanding of tree growth and health. Highlights: Forest ecosystems are usually developed on acidic and nutrient-poor soils. Bacteria and fungi play an important role in nutrient cycling and tree nutrition. The environmental drivers of the bacterial and fungal communities are not the same. Interactions between plant-microorganisms and between microorganisms need to be considered. Importance to bridge environmental microbiology to genomics for a better understanding of the forest ecosystem functioning.